2005
DOI: 10.1097/01.olq.0000175405.36124.3b
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use by Men Is a Risk Factor for the Acquisition of Sexually Transmitted Infections and Human Immunodeficiency Virus From Female Sex Workers in Mumbai, India

Abstract: Men who drink alcohol when visiting FSWs engage in riskier behavior and are more likely to have HIV and STIs. Prevention programs in India need to raise awareness of this relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 19 publications
4
55
0
4
Order By: Relevance
“…Our finding that alcohol use before sex is associated with unsafe sex with non-regular partners supports similar findings from other populations in India (e.g., Madhivanan et al, 2005). Taken along with findings of heavy and frequent drinking among wine shop patrons, the data suggest a need to address the role of responsible drinking and binge drinking in HIV prevention messages (e.g., see Carey, 2001).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our finding that alcohol use before sex is associated with unsafe sex with non-regular partners supports similar findings from other populations in India (e.g., Madhivanan et al, 2005). Taken along with findings of heavy and frequent drinking among wine shop patrons, the data suggest a need to address the role of responsible drinking and binge drinking in HIV prevention messages (e.g., see Carey, 2001).…”
Section: Discussionsupporting
confidence: 77%
“…Behavioral surveillance conducted by NACO shows that 75% of a nationwide sample of female sex workers consumed an alcoholic drink occasionally before sex; among their male clients, 23% reported drinking on a daily basis (National AIDS Control Organization, 2001). Other studies evaluating behavioral factors associated with sexual risk in India report that alcohol use is associated with heterosexual risk markers such as prevalent sexually transmitted diseases and sex with female sex workers (Madhivanan et al, 2005), extra-marital sex (Schensul et al, 2006) and non-use of condoms (Gupta, Sharma and Ramachandran, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In the general population, 40% (1 million) live in various slum pockets and almost 80% (2 million) are poorly educated (Pallikadavath, Garda, Apte, Freedman & Stones, 2005). It is hypothesised that because of the high traffic of rural commuters to and from cities like Ahmadabad 255 km to the north (where 13% of commercial sex workers are HIV-infected) and Mumbai 263 km to the south (where 54% of commercial sex workers are HIV-infected and injection drug use is more accessible), the epidemic may build a stronghold here (Fung et al, 2007;Madhivanan et al, 2005;Pallikadavath et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Second, preliminary studies by our team comparing a community-based sample to wine shops suggested that the wine shop sample had significantly higher sexual risk behaviors. 18 Finally, alcohol use has been associated with HIV and STDs and sex with female sex workers 19 and with behavior risk factors such as extramarital sex among men in urban India. 20 Driven by these reasons, we began our exploratory study.…”
Section: Introductionmentioning
confidence: 99%